Responses of lactating Holstein cows to differing levels and direction of supplemental airflow - Joseph P. Harner; John F. Smith; W.F. Miller; B. Cvetkovic (Kansas Agricultural Experiment Station Research Reports, 2004)
Seven heat-stressed, lactating Holstein cows were exposed to six different cooling systems to evaluate the effects of air velocity and direction of airflow. Cows were arranged in a 7 x 7 Latin-square design. Six cooling treatments were compared with a control. Supplemental airflow was provided by axial flow at one of three velocities: 500, 750, or 900 cubic feet per minute (CFM). Airflow was either from the front to rear (FRT) or from the right side (SIDE) of the cow. Combined cooling treatments were FRT-500, FRT- 750, FRT-900, SIDE-500, SIDE-750, or SIDE-900. All cooling systems used a lowpressure soaking system that operated 1 minute every 5 minutes. Respiration rates, rearudder skin surface temperature, and vaginal temperature were measured and recorded during 2 hours of treatment during seven hot and humid afternoons. Cooling systems reduced respiration rate, rear-udder skin surface temperature, and vaginal temperature. When airflow was 750 or 900 CFM, no differences were observed among treatments. When airflow was 500 CFM, rate of decline of rearudder skin surface temperature and vaginal temperature were reduced, compared with those of other treatments. These results indicate that there was no advantage to increasing airflow more than 750 CFM when using a low-pressure soaking system that wets the cattle every 5 minutes. Differences due to airflow direction were only observed when airflow was reduced to 500 CFM. At 500 CFM, airflow from head to tail was not as effective as from the side. Current recommendations of 750 CFM of airflow directed at the side of the cow are effective in reducing heat stress of lactating dairy cattle.; Dairy Day, 2004, Kansas State University, Manhattan, KS, 2004;
Keywords: Dairy Day; 2004; Kansas Agricultural Experiment Station contribution; no. 05-112-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 941; Dairy; Heat stress abatement; Cow comfort; Cow cooling